Preparation of CeO2 by a simple microwave-hydrothermal method - Riccardi, C. S. [UNESP]; Lima, R. C.; dos Santos, M. L. [UNESP]; Bueno, Paulo Roberto [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2009)
Cerium carbonate hydroxide (orthorhombic Ce(OH)CO3) hexagonal-shaped microplates were synthesized by a simple and fast microwave-hydrothermal method at 150 degrees C for 30 min. Cerium nitrate, urea and cetyltrimethylammonium bromide were used as precursors. Ceria (cubic CeO2) rhombus-shape was obtained by a thermal decomposition oxidation process at 500 degrees C for 1 h using as- synthesized Ce(OH)CO3. The products were characterized by X-ray powder diffraction, field-emission scanning electron microscopy, thermogravimetric analysis and Fourier transformed infrared spectroscopy. The use of microwave-hydrothermal method allowed to obtain cerium compounds at low temperature and shorter time compared to other synthesis methods. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Cerium compounds; Ceria; Microwave-hydrothermal method; Thermal decomposition oxidation